PROFILE OF JUNIOR HIGH SCHOOL STUDENTS ON SCIENCE PROCESS SKILLS - Tuti Lestari; Risher, Zhafirah Dosena (Pendidikan IPA, FMIPA, UNP, 2024)
The Curriculum in Indonesia has two elements in science learning, namely understanding science which is related to high-level thinking skills and process skills as an effort to hone thinking skills in investigation or research. In science learning, process skills that can be assessed are known as science process skills. Student need to have Science Process Skills (SPS) as preparation for facing the realities of life, so that student s are trained to think logically to solve problems. The research aims to measure students mastery of science process skills in general and differences in mastery of science process skills based on gender in mixed compound element material in class VIII SMP IT Dar El Iman Padang. This research is quantitative research with a descriptive survey. The sample selection used a total sampling technique, namely 4 classes. Data collection techniques were carried out by assessing student worksheets and written tests. The research results show that students’ mastery of science process skills has varying averages. The lowest mastery of SPS indicators is the hypothesis indicator with a percentage of 36,9% in the poor category and the highest indicator is the prediction indicator at 85.7% in the very good category. Based on gender, female students SPS mastery is better with a percentage 69.7 % in good category than male students with a percentage 58.0% in sufficient category. Overall, students mastery of science process skills is categorized as good at 63,3%.